Peningkatan Keterampilan Undha-Usuk Basa Melalui Implementasi Model Pembelajaran Bermain Peran pada Siswa Kelas IV - Nawangsari, Fika; Purwandari, Septiyati; Malik, Muh Syauqi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
The main problem identified in this study was the low ability to communicate in everyday Javanese in school and home environments. To overcome this problem, the study used a role-playing learning model approach. This study aims to improve Javanese language skills, especially undha-usuk basa, among grade IV students of SDN Pabelan 3. This study was conducted by involving grade IV teachers and 15 students. The research method used is mixed with a type of classroom action research. Over the two cycles, data were collected through activities, written tests, observations, interviews, documentation, and field notes. Data analysis was carried out quantitatively and qualitatively. The results showed a significant improvement in students' basic skills after applying the role-playing learning model. This change is reflected in the percentage increase in the learning process, pretest results, cycle I posttest, and cycle II posttest. This study emphasizes the importance of support from families and teachers in helping students practice communicating in Javanese following undha-usuk basa. This is expected to form positive student character, such as a sense of care, love, and pride in their local language. Therefore, maintaining and improving Javanese language skills is essential in preserving the language and culture of the region.